2018
DOI: 10.1080/07420528.2018.1497642
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning of female nurses during the night shift: The impact of age, clock time, time awake and subjective sleepiness

Abstract: Decline in cognitive functioning in the workplace is a major concern for health care systems. Understanding factors associated with nighttime functioning is imperative for instituting organizational risk management policies and developing personalized countermeasures. The present study aims to identify individual factors associated with cognitive functioning during the night shift of hospital nurses working on irregular rotating-shift schedules. Ninety-two female nurses were recruited from 17 wards in two gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
0
19
1
Order By: Relevance
“…While omission errors reflect accuracy, the number of correct responses on the DSST and LCT capacity reflect performance speed. Thus, the authors speculate that the speed aspect of visuomotor performance tasks is especially influenced by homoeostatic sleep drive (Zion & Shochat, ) and, therefore, that a short nap aimed to offset this influence may benefit performance speed more than accuracy. These findings are consistent with those of other field studies showing improved speed performance on vigilance tasks following a short nap during the night shift (Purnell, Feyer, & Herbison, ; Signal, Gander, Anderson, & Brash, ; Smith et al, ; Smith‐Coggins et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While omission errors reflect accuracy, the number of correct responses on the DSST and LCT capacity reflect performance speed. Thus, the authors speculate that the speed aspect of visuomotor performance tasks is especially influenced by homoeostatic sleep drive (Zion & Shochat, ) and, therefore, that a short nap aimed to offset this influence may benefit performance speed more than accuracy. These findings are consistent with those of other field studies showing improved speed performance on vigilance tasks following a short nap during the night shift (Purnell, Feyer, & Herbison, ; Signal, Gander, Anderson, & Brash, ; Smith et al, ; Smith‐Coggins et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors previously demonstrated biopsychosocial factors that are associated with night shift sleepiness and performance (Zion et al, ; Zion & Shochat, ). The current study shows that the effects of a scheduled nap on sleepiness and performance are significant above and beyond the effects of biopsychosocial factors that are independently associated with night shift performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, during the 12-h night shift, nappers took advantage of the opportunity to nap, yet their sleep efficiency at home was compromised. It is likely that individual differences that are associated with adaptation to shiftwork, such as age, chronotype, cognitive arousal, responsibilities, and sleep opportunities at home, may underlie these different adaptation strategies [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses who work at night or in rotating shifts rarely have sufficient amounts of sleep. Sleep loss is cumulative, and after a while, the sleep debt may be significant enough to impair integration of information, cloud decision-making, and interrupt planning, plan implementation and vigilance [43]. Insufficient sleep has been associated with mood and cognition changes, lower quality job performance, declined motivation, safety risks and physiological complains [44,45].…”
Section: Correlation Among Cs and Rest And Leisurementioning
confidence: 99%